Note sull’artificialità della vita - Clarizio, Emanuele (Mechane, 2020)
Material support for every kind of genetic modification and moral support for disparate instances of power that aim at its discipline and exploitation, human life is according to Ivan Illich the victim of an institutional fetishization. In order to overcome this situation, he hopes for an “epistemological asceticism” that takes life away from the wires of institutions. However, it is possible to show – as Yan Thomas did studying Roman law, and Georges Canguilhem in reference to ecology – that life is in fact the fruit of technical and social institutionalization. Therefore, rethinking a politics of life is not possible if we don’t problematize the relationship that it has always had with technology.